PENGARUH PELVIC ROCKING EXERCISE DENGAN BIRTHING BALL TERHADAP KEMAJUAN PERSALINAN PADA IBU PRIMIPARA - Putri Lia Prasetyani; Qomariyah; Resa Nirmala Jona (Pusat Riset dan Inovasi Nasional, 2023)
Prolonged delivery is a contributing factor to the mortality rate of mothers with a prevalence of 20% in Demak regency. Based on the survey in First Clinic Irma Solikin, Mranggen district, Demak regency, the birth data in January 2022 showed that 40% of mothers of 15 mothers experienced prolonged partity. One of the physiological efforts to prevent prolonged delivery is promoting pelvic rocking with a birthing ball. This technique requires the mothers to sit on the ball and rock the ball. This action makes the mothers feel comfortable and help them to promote the delivery due to the influence of gravity force. Thus, the fetus or the lower part of the fetus could move to the pelvis and shorten the delivery time. This research determined the influence of pelvic rocking exercise with a birthing ball on the delivery advancement of primipara mothers. The sample consisted of 20 mothers in the intervention group with pelvic rocking intervention with a birthing ball. Then, the other 20 mothers in the control group received normal delivery. The applied instruments were an observation sheet and a partograph. The researchers analyzed the data with univariate and bivariate analyses. The results found the influence of pelvic rocking exercise with birthing ball technique toward the delivery progress of primipara mothers in the First Clinic, Irma Solikin, Mranggen district, Demak regency. Keywords: Pelvic Rocking, Birthing ball, Delivery progress, Primipara mothers